Contributions to the history of teacher unionism in Portugal: From study groups to the assertion and crisis of the teacher union movement - Manuel Tavares (Arizona State University, 2014)
This paper focuses on the origins of the teachers' union in Portugal, making an historical journey through the associations of the 19th century and the first demonstrations of the trade unions in the first Republic. In the light of history, it is intended to analyze the emergence of the Teachers' Union, in Portugal, and their paths in the decades of the 1970's and 1980's of the 20th century, and to present some of the reasons that have contributed to a substantial change in teachers' union from the decade of the mid 1980's. We will give particular attention to the roots of the contemporary teacher unionism that are found in the Study Groups of the Teaching Staff of the Secondary Education (GEPDES) and which constitute a movement of reflection and claims in anticipation of the teachers unions that were formed in the days followed by the April revolution. The empirical study was carried out by means of interviews with four of the main protagonists of this movement and reveals the goals, the political consciousness of its members, the possible influences of the Communist Party, and the importance of this movement in emergency and affirmation of the teachers' union. It is a reflection on the conditions existing in Portugal in post- April 25th, 1974, and about the conditions that have emerged from the second half of the 1980s, especially with the advancement of economicist and neo-liberals policies, who have contributed to a certain decline and crisis of the teacher union movement as to the crisis of professional identities of teachers. The teachers union was constituted as a reflexive movement drifting away, gradually, from the references of the labor movement, stating at the same time its specificity and autonomy.